(untitled) (Homoeopathy for All, 2024)
Hypothyroidism is a condition where your thyroid gland does not produce enough thyroid hormone which leads to slow metabolism. Person started feeling tired, Hair fall, weight gain, aversion to do daily activities, unable to tolerate cold temperatures. In this article we will see the efficacy of individualized ho moeopathic medicine CALCAREA CARBONICA in treating the cases of 46 years old lady.